Belgium : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Belgium. (IMF Staff Country Reports; Country Report, 2019)
This Article IV Consultation highlights that Belgium has experienced nine consecutive years of economic growth. Per capita GDP has surpassed pre-crisis levels, and unemployment is at its lowest level in four decades. The financial sector has also undergone structural changes and increased its resiliency to shocks. The authorities have implemented important reforms in recent years that have contributed to job creation, improved competitiveness, and lowered the deficit. However, the reform agenda is unfinished, and the new government should take advantage of the still favorable economic conditions to press ahead with further reforms to strengthen the resilience and growth potential of the economy. The priority should be to rebuild fiscal buffers by gradually moving toward a balanced budget in the medium term, supported by efficiency-oriented spending reforms. It is also imperative to boost productivity growth by supporting entrepreneurship, increasing investment in infrastructure, strengthening competition in services, and fostering innovation.